2002
DOI: 10.1093/ajcn/76.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Dietary catechin delays tumor onset in a transgenic mouse model

Abstract: Physiologic intakes of specific dietary polyphenols, such as catechin, may play an important role in cancer chemoprevention. Wines have different polyphenol concentrations and compositions; therefore, the overall health benefits of individual wines differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…The procyanidins, epicatechin and catechin, have strong antioxidant activity and have been found to inhibit low density lipoprotein (LDL) oxidation in vitro [49]. In mice, catechin inhibits intestinal tumor formation and delays tumors onset [50,51]. Sawa et al (1999) found that chlorogenic acid has very high alkyl peroxyl radical (ROO•) scavenging activity.…”
Section: Apple Phytochemicalsmentioning
confidence: 99%
“…The procyanidins, epicatechin and catechin, have strong antioxidant activity and have been found to inhibit low density lipoprotein (LDL) oxidation in vitro [49]. In mice, catechin inhibits intestinal tumor formation and delays tumors onset [50,51]. Sawa et al (1999) found that chlorogenic acid has very high alkyl peroxyl radical (ROO•) scavenging activity.…”
Section: Apple Phytochemicalsmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / m s e c rodent models [19]. An irreparable DNA damage leading to G2/M arrest and apoptosis selectively in head and neck squamous cell carcinoma was also reported by Shrotriya et al [20].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 70%
“…Her-2 is often overexpressed in metastatic cancers including the MDA-MB-435 cell line that was used for this study. The monomeric form of catechin constitutes up to 65 70% of total red wine polyphenols and has been shown to delay tumor initiation [10,15,16]. Resveratrol, quercetin, and catechin are all viable chemopreventives because they are absorbed and metabolized rapidly in vivo and can be detected in plasma and urine samples in the intact form in humans and rodent models [17 20].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has proapoptotic, antigrowth, anti-inflammmatory, antiangiogenic, and anti-invasive properties that makes it an attractive anticancer compound (12)(13)(14). Much of the data on potential anticancer properties of resveratrol has been shown in vitro with high concentrations of resveratrol ranging from 30-200 µM (15)(16)(17)(18)(19)(20)(21). We and others have shown that resveratrol at 50 µM can inhibit cell migration and invasion (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%